Regioselective bromination of aryl ureas with Phenyliodine(III) diacetate and potassium bromide. Issue 44 (1st November 2019) - Wang, Chun-Meng; Du, Jian-Yao; Zhang, Jin-Yang; Tang, Kai-Xiang; Gao, Tian-Hong; Xu, Yun-Gen; Sun, Li-Ping
Abstract: An efficient regioselective and operationally simple urea bromination method utilizing PIDA and potassium bromide is reported. This protocol proved to be effective on a broad range of substituted ureas in acetone at room temperature, forming the p -brominated compounds in 44–86% yields. Graphical abstract: Image 1 Highlights: A novel and efficient protocol of metal-free aryl C–H bond bromination of ureas has been developed, in which simple and readily available bromide salt is employed as the bromine source. This convenient conditions make this protocol very easy to handle and practical. Besides, the present method tolerates a variety of functional groups and allows the synthesis of diverse 4-brominated urea derivatives in moderate to excellent yields.